A Comprehensive Failure Risk Analysis of Drainage Pipes Utilizing Fuzzy Failure Mode and Effect Analysis and Evidential Reasoning - Zinan Wang; Yuxuan Yang; Hao Wang; Xuming Zeng (Buildings, 2023)
Drainage pipes play a crucial role in maintaining the functionality of cities and ensuring the smooth flow of daily life for its inhabitants. However, due to their placement either in shallow ground or within building foundations, maintenance of these pipes can be challenging. At present, research in this field primarily focuses on evaluating the overall health of macroscopic pipeline systems. Moreover, there is a lack of decision algorithms that can effectively minimize the subjectivity of experts. To address this issue, a failure risk analysis method was developed that incorporates the principles of Failure Mode and Effect Analysis (FMEA), Evidential Reasoning (ER), and Fuzzy Set Theory (FST) (FACEF). Nineteen pipeline failures were analyzed by synthesizing information from five commonly used pipeline evaluation specifications. Ten experts were consulted to evaluate these failures, and the scores were calculated and ranked using the FACEF method. The results indicated that six types of failures, namely penetration, crack, deformation, mismatch, leakage, and obstruction, require the most attention. An analysis of the typical causes of failure was conducted based on the FACEF scores, and measures for prevention and control were recommended. This study provides novel perspectives and insights on the risk management of pipeline failures, with a focus on reducing the influence of expert subjectivity through the refinement of pipeline failure analysis.